Sistem Pakar untuk Mengidentifikasi Jenis-Jenis Kayu - Uning Lestari (JUITA : Jurnal Informatika, 2011)
Application of expert system currently has entered most aspects of human life. The purpose of creation of expert system is adopting an expert knowledge into computer applications in order to solve the real problem that can only be resolved by experts. The process of identifying a type of wood can only be done by experts that are experienced in the identification and properties of wood. This study adopts the expert’s knowledge of identification and properties of wood in computer application that produced an expert system to identify the wood based on the physical characteristics of wood including wood general characteristics yields the color, pattern, texture, direction of the fiber, gloss, the impression of sense, violence. Wood anatomical characteristics of leaf width is includes: kinds of cells and functions, vessels, vessels of the distribution, composition, shape of vessel perforation vessel, the contents of fields (parenkima and wooden fingers), growing place and durability class. This research uses a rule-based reasoning and forward chaining inference engine. Knowledge base gained from interviews with experts the identification and properties of wood, as well as literature supporting literature. This computer application system was created by using Delphi 7.0. From the testing that has been done obtained a conclusion that the expert system application that is created is capable of identifying type of wood based on the physical properties of wood are entered by the user